Job matching in connected regional and occupational labour markets - Alexandra Fedorets; Franziska Lottmann; Michael Stops (Regional Studies, 2019)
Job mobility equilibrates disparities in local labour markets and influences the job-matching efficiency. We specify a matching function with regional, occupational and combined regional–occupational spillovers of unemployed and vacancies. To construct these spillovers, we use information on regional proximities and occupational similarities. Based on novel German data on new hires, the unemployed and vacancies, we find significant positive effects of all spillover terms, with the exception of the negative and significant spillovers of the unemployed in other occupations. The reverse spillover effects could be used for designing macro-oriented policies aiming to improve job matching.
Keywords: C21; C23; J44; J64; 330; Matching function; Job mobility; Local labour market